APAKAH OPINI AUDIT MERUPAKAN SEBUAH GOOD NEWS? PENGUJIAN TEORI SIGNALING - Dwi Ratmono; Dias Nurmalasari (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2015)
The objective of this study is to examine the effect of audit opinion and change in audit opinion on reporting delay. The auditor switch, the new accounting standard, unexpected earnings, leverage and profitability used ascontrol variables. This study proposes hypotheses that the audit opinion which is better than the previous year will negatively affect reporting delay. Meanwhile, change in audit opinion better than the previous year will negatively affect on the reporting delay. Samples of this research is 170 manufacture firms listed in Indonesian Stock Exchange in year 2011-2012 that selected by using purposive sampling method. The technique of analysis used for examining the hypothesis is multiple regressions. The result of this research that audit opinion and change in audit opinion negatively affects reporting delay. Firms that receiving unqualified audit opinion and audit opinion better than the previous year gave a good news for investors so as to reduce the reporting delay.